Clay Shoveler's fracture in a volleyball player - Hetsroni, I.; Mann, G.; Dolev, E.; Morgenstern, D.; Nyska, M. (The Physician and Sportsmedicine, 2005)
Clay shoveler's fracture is a repetitive stress injury that affects the spinous process of the lower cervical and upper thoracic spine. In sports, deceleration forces caused by the pull of the trapezius, rhomboids, and the ligamentum nuchae on the neck probably exert repetitive traction on their attachment sites to the narrow spinous processes. The condition is known in manual laborers, but it is rare in athletes, as in this case of a volleyball player. Early recognition and treatment with rest, analgesics, and physical therapy are important to prevent debilitating chronic back pain.